(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study delves into the multifaceted landscape of customer satisfaction in online banking services in Pune, aiming to provide nuanced insights into user perceptions, challenges, and areas for improvement. The objectives of the research encompassed exploring various aspects of customer satisfaction, analysing the reasons for ‘Customer Dissatisfaction’, and evaluating the impact of different dimensions of online banking services on customer satisfaction. To achieve these objectives, a comprehensive research methodology was employed. A survey involving 100 individuals from diverse socio-economic backgrounds in Pune was conducted, utilizing a questionnaire disseminated through various digital platforms. The responses gauged satisfaction and dissatisfaction levels, reasons for dissatisfaction, and opinions on different dimensions of online banking services. The data collected were subjected to statistical analysis, including mean scores, standard deviations, and regression analysis. The results revealed significant findings across various dimensions. The pie chart representation indicated that 63% of respondents were satisfied, while 37% expressed dissatisfaction with online banking services. Mean scores and standard deviations provided a detailed examination of aspects influencing customer satisfaction and dissatisfaction, highlighting specific strengths and pain points. The regression analysis validated hypotheses related to the impact of the user interface, convenience and flexibility, and transaction speed and reliability on customer satisfaction. Based on these findings, key suggestions include continuous enhancement of the user interface, prioritizing convenience and flexibility features, addressing security concerns, streamlining transaction processes, and strengthening customer support services. These recommendations aim to foster an environment that is not only technologically advanced but also aligns with the diverse needs and expectations of the online banking user base in Pune.